The influence of transformational leadership and job training on employee performance at PT. Adira Finance Yogyakarta, with job satisfaction as an intervening - Dimas Arya Janti; Trias Setiawati; Andriyastuti Suratman (Jurnal Mantik, 2023)
Several companies, including those in the finance industry, have seen a drop in employee performance. Stagnation in leadership and training models has decreased performance indicators. This study aims to figure out how a transformational leadership style and training affect the performance of PT Adira Multifinance Tbk. Employees, with job satisfaction as a mediator. The quantitative method was used by giving questionnaires to 35 office workers at the Yogyakarta branch of PT Adira Multifinance Tbk. This was accomplished via quota sampling. Directly collected data were analyzed using simple and multivariate linear regression. So, human resources are an essential part of corporate governance, and PT Adira Multifinance Tbk in Yogyakarta needs them to be successful. Confirmation of the hypothesis suggests transformational leadership and employee training partially affect employee performance. In addition, transformational leadership styles and employee training partially affect employee satisfaction. Lastly, tests done simultaneously showed that transformational leadership styles improve employee performance by making employees happier, and employee training improves employee performance by making employees happier. As a result, the whole hypothesis was accepted, and a significance value of 0.05 was used to test it. The better the transformational leadership model and job training in a company, the greater job satisfaction there will be, which will have implications for improving performance.